1966
DOI: 10.1042/bj0990682
|View full text |Cite
|
Sign up to set email alerts
|

Protoplast formation and yeast cell-wall structure. The action of the enzymes of the snail, Helix pomatia

Abstract: 1. The digestive juice of the snail Helix pomatia was used in the study of the degradation of isolated cell-wall preparations from a strain of Saccharomyces carlsbergensis. 2. The crude enzyme system was fractionated by gel filtration and the activities of the more specific fractions thus obtained were examined. 3. Results are discussed with respect to (a) the nature of various factors that are essential for protoplast formation and cell-wall dissolution and (b) structures envisaged in yeast cell walls that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1968
1968
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Maintenance of these bonds in a reduced state might keep the cells sensitive to sphaeroplast formation. This hypothesis would be consistent with the observation that thiol reagents which reduce disulphide bonds may render yeasts more sensitive to sphaeroplast formation (Anderson & Millbank, 1966). As a test of this hypothesis, exponential-phase yeasts were treated with I ,ug cycloheximide/ ml, an inhibitor of protein synthesis (Kerridge, 1958).…”
Section: Eflect Of Cycloheximide On Sensitivity To Sphaeroplast Formasupporting
confidence: 74%
See 1 more Smart Citation
“…Maintenance of these bonds in a reduced state might keep the cells sensitive to sphaeroplast formation. This hypothesis would be consistent with the observation that thiol reagents which reduce disulphide bonds may render yeasts more sensitive to sphaeroplast formation (Anderson & Millbank, 1966). As a test of this hypothesis, exponential-phase yeasts were treated with I ,ug cycloheximide/ ml, an inhibitor of protein synthesis (Kerridge, 1958).…”
Section: Eflect Of Cycloheximide On Sensitivity To Sphaeroplast Formasupporting
confidence: 74%
“…Sometimes yeasts may be rendered more sensitive to sphaeroplast formation by treatment with thiol reagents such as thioglycollate (Khvac, Bednarova & Greksak, I 968), a-mercaptoethanol (Darling, Theilade & Birch-Anderson, I 969) or dithiothreitol (Sommers & Lewis, 1971). It has therefore been suggested that the presence or absence of disulphide bonds within the protein component of the wall affects the penetration of the degradative enzymes and thus the sensitivity to sphaeroplast formation (Anderson & Millbank, 1966 …”
Section: Introductionmentioning
confidence: 99%
“…74S) but does not occur on old cells unless they are pretreated with mercapto-ethanol. 3 The action of glucanases on the walls of different genera of yeast has allowed them to be divided1'1 into four classes as follows: (i) Those yeasts such as Saccharomyces whose walls are hydrolysed completely by jS-1,3 glu canases but only weakly or incompletely by /3-1.6 glucanases. (ii) Those such as Hansenula and Nadsoma which are completely hydrolysed by both types of glucanase.…”
Section: Enzymic Hydrolysis Of Wall Componentsmentioning
confidence: 99%
“…Penetration of the cell by mercury may occur by a number of possible mechanisms. If mercury is associated with a high-affinity anion such as chloride, two quite probable mechanisms are that the mercury may permeate the envelope as an essentially uncharged species (Cotton & Wilkinson, 1962) or may bind to the membrane itself and, as a consequence, render the membrane permeable to mercury. The present study sheds no light upon these alternatives but does indicate the fact of mercury penetration.…”
Section: Discussionmentioning
confidence: 99%
“…Helicase solubilized a significant fraction of the sodium hydroxide-extracted residue, suggesting that there may have been a considerable protein fraction not released by sodium hydroxide because of association with wall glucan. However, since the activity of Helicase upon yeast cell walls has been deduced from studies on unextracted walls (Anderson & Millbank, 1966), there is a great deal of uncertainty as to the correct interpretation of this result. For this reason a further experiment using both Pronase and Helicase digestion was performed upon unextracted walls ( Table 2).…”
Section: R E S U L T Smentioning
confidence: 99%